A 30-Year-Single-Center Experience in Atrial Myxomas: From Presentation to Treatment and Prognosis - Obrenović-Kirćanski, Biljana; Mikić, Aleksandar; Parapid, Biljana; Djukić, Petar; Kanjuh, Vladimir; Milić, Nataša; Kovačević-Kostić, Nataša; Velinović, Miloš; Seferović, Petar; Vraneš, Mile (The Thoracic and Cardiovascular Surgeon, 2013)
Background The symptoms of myxoma are atypical, vary greatly, and may mimic numerous conditions. Our aim was to investigate the correlation of localization, size, and consistency of myxoma with its treatment and prognosis.Methods Over a span of 30 years, 74 consecutive patients (24 men, mean age 46.7 years) were surgically treated for echocardiography-diagnosed myxomas at our center.Results Left atrial myxomas were more frequent (89.19%), with the racemous form being predominantly left-sided and having no difference in tumor size regardless of localization. Three patients were asymptomatic; and those who were symptomatic, symptoms appeared 2 to 36 months (mean 13.60 ± 7.52) before diagnosis. Nonspecific symptoms and signs were present in 91.98% of patients, whereas specific symptoms and signs were present in 74.32%. More often, patients with myxomas >5 cm in diameter were symptomatic. Embolic events occurred in 15 patients (9 cerebral, 4 pulmonary, 2 peripheral), more frequently in right atrial myxomas of >5 cm diameter. All patients were surgically treated on diagnoses, with no intraoperative mortality or recurrences.Conclusions Symptoms in our cardiac myxoma patients were more pronounced when the myxomas were left-sided, racemous, and over 5 cm in diameter. Even in asymptomatic patients, a high index of suspicion assured timely diagnosis and management.
Keywords: atrial myxomas; preoperative symptoms; influence